2019
DOI: 10.1007/s10854-019-00899-9
|View full text |Cite
|
Sign up to set email alerts
|

Ultransonic-assisted alcoholysis preparation of BiOClxBr1−x modified BiOF microstructure with enhanced photocatalytic performance

Abstract: A series of BiOF/BiOCl x Br 1−x composites with different BiOF contents have been synthesized by means of ultrasonicassisted alcoholysis for the first time. The as-prepared samples were characterized by such methods as XRD, SEM, TEM, EDS, Mapping, BET, UV-Vis, XPS and PL spectra. The photocatalytic activity of samples under visible-light irradiation was evaluated by the degradation of Rhodamine. The results revealed that BiOF/BiOCl 0.75 Br 0.25 composite exhibited much higher photocatalytic activity than pure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…As for the high‐resolution XPS spectra of the Cl 2p (Figure 4e), two main peaks at 196.5 and 198.4 eV appeared in the as‐prepared Bi/BiOCl x Br 1− x films (except at x = 0, BiOBr), which are attributed to Cl 2p 3/2 and Cl 2p 1/2 , respectively. [ 42 ] Meanwhile, the intensity of these peaks was found to increase with the increase in the chlorine ratio in the as‐prepared Bi/BiOCl x Br 1− x films. In addition, there was another peak that appeared in the XPS Cl 2p spectrum of BiOCl which is usually ascribed to chemical bonds between chlorine and organic species.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As for the high‐resolution XPS spectra of the Cl 2p (Figure 4e), two main peaks at 196.5 and 198.4 eV appeared in the as‐prepared Bi/BiOCl x Br 1− x films (except at x = 0, BiOBr), which are attributed to Cl 2p 3/2 and Cl 2p 1/2 , respectively. [ 42 ] Meanwhile, the intensity of these peaks was found to increase with the increase in the chlorine ratio in the as‐prepared Bi/BiOCl x Br 1− x films. In addition, there was another peak that appeared in the XPS Cl 2p spectrum of BiOCl which is usually ascribed to chemical bonds between chlorine and organic species.…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding bandgap energy of the as‐prepared Bi/BiOCl x Br 1− x films was estimated from the plots of ( αhv ) n /2 versus hv (Figure 5b) to be 2.5, 2.6, 2.7, 2.9, and 3.2 eV for Bi/BiOBr, Bi/BiOCl 0.2 Br 0.8 , Bi/BiOCl 0.5 Br 0.5 , Bi/BiOCl 0.8 Br 0.2 , and Bi/BiOCl, respectively. [ 42 ] The bandgap energy was gradually decreased with the increase of the Br:Cl molar ratio indicating the modulation of their band structure upon changing the molar ratio. Previous studies [ 42,44 ] reported that there is no change in the positions of the conduction band (CB) bottom upon increasing od Br content, whereas those of valence band (VB) top gradually uplift providing the higher absorption intensity of the visible‐light irradiation upon the increasing of Br content in the solid solution.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations